Eficiencia de varias dosis y fuentes potásicas en maíz amarillo duro bajo condiciones del Valle del Rio Carrizal - Loor Barderrama, Gema Katherine (2020)
The research was carried out during the dry season of 2019 in the locations of El Limón and El Morro in the Bolívar canton. The objective of this research was to assess the efficiency of various doses and potassium sources on productivity in hard yellow corn under conditions of the Carrizal River Valley. The treatments consisted of four sources of potassium (K); (Korn kali, Yaramilla hydran, Sulfate of K and Muriate of K), three levels of K (100, 150 and 200 kg ha-1) and a witness with omission of K. The design used was randomized complete blocks with factorial arrangement A x B + N, with 13 treatments, three replicas and 39 experimental units. The main variables recorded were grain yield (kg ha-1), K agronomic efficiency (EAK) and net benefit of potassium fertilization. The yield was not influenced (p> 0.05) by the sources and doses of K tested in any of the locations evaluated. The orthogonal contrast analysis between potassium treatments vs. the control with omission of K showed significant statistical differences (p <0.05) in both locations evaluated. In El Morro and El Limón, potassium fertilization increased the yield by 18.91 and 33.26, respectively, in relation to the control, regardless of the sources and doses of K. The highest EAK was achieved in both El Morro and El Limón with the dose of 100 kg ha-1 of K, with 21 and 25 kg of grains kg-1 of K applied. In both locations, potassium muriate in doses of 150 kg ha-1 reached the highest net economic benefit with 920 and USD 891 ha-1.